Innovative Coffee Roasting Machine with Sorting and Packaging System in Alamendah Tourism Village - Siboro, Milson; Daliana, Nadia; Maharani Puteri , Aura; Latifa Santoso, Diesya; Dwi Prasetio, Murman (International Journal of Innovation in Enterprise System, 2025)
Coffee is one of the agribusiness commodities highly sought after by many MSME players, especially in Bandung Regency, West Java. However, the Assisted Unit of Alamendah Tourism Village faces challenges such as inconsistent coffee quality, unstable roasting temperatures, and low efficiency in sorting and packaging. Through the Student Creativity Program for the Application of Science and Technology (PKM-PI), an Innovative Coffee Roasting Machine with an Automated Sorting and Packaging System was developed using the Design Thinking methodology. The implementation of this innovation increased production from 110 kg to 210 kg per month (a 90% increase). The cooling machine reduced cooling time by 50%, ensuring more consistent coffee bean quality. Automated sorting improved classification accuracy, minimizing product defects. With this innovation, the MSME-scale coffee agribusiness sector has greater opportunities for sustainable growth. This automated sorting and packaging technology also has the potential to be applied on a larger scale, thereby enhancing the competitiveness of the local coffee industry in both national and international markets.